(untitled) (Baghdad Science Journal, 2024)
The objective of this research is to concentrate on the gray-tone spatial-dependence matrices to extract the texture features of the wounded skin treated with an alum solution activated with plasma. This method depends on the manual selection of the region of interest, which results in the dependence of parameter values on the extracted region. Potassium alum is used to clean and treat wounds, as well as to prevent bacteria from spreading, where the aqueous solution has aluminum hydroxide which forms a white precipitate on the wounds that works to coagulate the blood and stop bleeding, its efficiency increases when activated by plasma. A group of mice were used; their ages ranged from 2–3 months and their weight ranged from 200–250 g. Wounds were created in mice, and the experiment included using alum in the form of powder, an aqueous solution, and an aqueous solution activated with plasma for a duration of 5 minutes. The textural analysis investigated the effect of alum powder and alum solution on wounds and skin. According to the results of the textural analysis, the histopathology image and gray-tone spatial-dependence matrices, the skin regained its external appearance (near normal), and the wounds healed quickly as a result of employing the plasma-activated aqueous solution. The results were investigated from the histopathology images.